Artikel Urgensi Pengaturan Tindak Pidana Adat Dalam Peraturan Tertulis Pasca Pengesahan Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana - Muhamad Khalif Ardi; Muhammad Ikhsan Kamil; Devi Triasari; Doris Rahmat (Wacana Hukum, 2023)
Criminal law's legality principle limits offenses to those specifically established by law. In Indonesian Criminal Code (KUHP) enlarged the definition of criminal offenses beyond those in legislation. It now includes usual criminal offenses. However, customary criminal offenses are not explicitly regulated by law. This paper discusses the need of regulating customary criminal offenses in criminal law enforcement. This project also develops conceptual frameworks for transforming customary criminal offenses into codified laws. Normative legal research, or doctrinal legal research, examines legal norms and regulations. A literature evaluation of relevant legislative rules is used to collect and analyze data for this research. This analysis indicates that written legislation should provide thorough regulations on customary criminal offense structure. These rules aim to reduce the arbitrary and inconsistent use of customary criminal law in criminal justice. The study's findings also show that written legal rules, such as Regional Regulations, can be used to formulate customary criminal offense regulations that comply with legality.